Dental Caries Experience and Oral Health Related Quality of Life in Working Adults - Omair M. Bukhari (Saudi Dental Journal)
Objective: To evaluate effect of dental caries experience and untreated dental decay on Oral Health-Related Quality of Life (OHRQoL) in working adults. Methods: The clinical records of 160 patients were reviewed. Dental health indicators were derived from individual tooth- and surface-level data allowing for calculating the number of decayed surfaces (D), number of decayed missed filled surfaces (DMFS), and significant caries (SiC) indices. A questionnaire was administered to verify demographic factors and OHRQoL. The questionnaire was administered via face-to-face interview, for patients in the hospital; or via telephone interview, for those who could not complete it during their hospital visit. Models were developed using multivariable linear regression to predict total OHIP-14 scores and examine the simultaneous association of independent and outcome variables. The model was adjusted for age, gender, and nationality.. Results: Physical limitation and psychological discomfort were the most frequent impacted domains, affecting 17.1% and 7.5% of subjects, respectively. Painful aching was the most frequent item to have any impact, affecting 64.4% of the subjects. The results of multivariable analysis indicated that the SiC score could statistically significantly predict the Oral Health Impact Profile (OHIP) score, P=0.0003. In the linear regression model, for participants with DMFS equal to or higher than the SiC, on average, OHIP scores were almost 10 points higher than for participants with DMFS below the SiC. Conclusion: The more the dental decay the higher the impact on OHRQoL. From a dental public health perspective, using OHRQoL as a need assessment tool, along with dental clinical indicator, can be helpful in planning and targeting public health programs for the most in-need adult populations. Clinical Significance: This study identified that patients with severe dental caries report poorer OHRQoL. Clinicians should be aware of impacts that dental decay may have on OHRQoL, including physical, psychological concerns, and pain.